Analysis of Soil Physical Properties (Texture, Bulk Density, and Permeability) in Jatirono Cocoa Garden, Banyuwangi Regency - Salsabila, Nabila; Anggraini, Firdha Kusuma Ayu; Prihandono, Trapsilo (Jurnal Ilmu Tanah dan Lingkungan, 2025)
Kalibaru District is an area in Banyuwangi Regency that has quite a large potential in the agricultural sector, such as Jatirono cocoa farming in Kajarharjo Village. However, the condition of the cocoa plants which tend to be dry and the fruit yields are less than optimal is one of the reasons this study was conducted. The purpose of this study was to determine the factors causing less than optimal growth of cocoa plants by analyzing the physical properties of the soil such as texture, bulk density, and soil permeability. The research methods used were survey methods and laboratory analysis. The soil sampling points for laboratory analysis were taken at 5 points (A, B, C, D, E) with point A as the center point, then points B and D were 50 meters from point A, while points C and E were 62.5 meters from point A. The results obtained for the texture indicators from the five sample points were sandy loam and clay, for the bulk density indicator the results were medium and high, and for the permeability indicator the results were fast and rather fast. So it can be concluded that the sandy clay texture with a more dominant percentage of sand fraction has a texture that tends to be coarse, this texture affects the bulk density of the soil where sand has a greater bulk density compared to clay, this texture also causes the soil's ability to pass water high or fast.